Green Manure Species for Phytoremediation of Soil With Tebuthiuron and Vinasse - Ferreira, Luziane Cristina; Moreira, Bruno Rafael de Almeida; Montagnolli, Renato Nallin; Prado, Evandro Pereira; Viana, Ronaldo da Silva; Tomaz, Rafael Simões; Cruz, Jaqueline Matos; Bidoia, Ederio Dino; Frias, Yanca Araujo; Lopes, Paulo Renato Matos (Frontiers in Bioengineering and Biotechnology, 2021)
The use of tebuthiuron for controlling weeds in sugarcane crops is usual. This herbicide is highly toxic and can persist in soil from 1 to 2 years by its degradation half-life. Hence, its residual is very hazardous for environment and society via leaching, surface runoff and carryover away from the agroecosystem. Screening out of species of green manure as potential phytoremediators for tebuthiuron in soil, with and with no vinasse, accordingly is the scientific point of this study. Green manure species selected for the trial in greenhouse were jack bean (Canavalia ensiformis), pigeon pea (Cajanus cajan), velvet bean (Mucuna pruriens) and millet (Pennisetum glaucum), and Crotalaria juncea as bioindicator of this herbicide. The determination/quantification of height, stem diameter and number of leaves in all plants were monitored and other morphological traits for drafting any inference about performance included biomass production of mass. Moreover, ecotoxicity bioassays were performed from soil samples at the beginning and the end of the experiment. Results showed a preliminary evidence for M. pruriens and P. glaucum capacity for effectively phytoremediating the soil with tebuthiuron as supported the development of C. juncea. Gompertz approach and principal component analysis, collectively, predicted these green manure species to grow healthier and longer in soil with tebuthiuron and vinasse and, thus, reduce physiological anomaly by ecotoxicity. The findings of this study are timely and should be of great relevance to development and implementation of cost-effective strategies targeting decontamination of tebuthiuron in sugarcane crops with vinasse application in fertigation.